PENGARUH PROMOSI, HARGA DAN PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN TOYOTA DYNA DENGAN JENIS USAHA SEBAGAI VARIABEL MODERASI (Studi Kasus Konsumen PT. New Ratna Motor, Semarang) - Afifi, Fahmi Rezqa; Ngatno, Ngatno (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2016)
Goal of companies is become the market leader of their products. To achieve it, companies have to increase their sales volume. As Toyota brand holder in Central Java and DIY, PT. New Ratna Motor always tries to lead the market share in all car types, including two-tonnage vehicles (truck) class. Toyota Dyna becomes the favorite of Toyota in this class, which the competition in this class is tighter. Promotion, price, and service are some of important factors which can be related with consumer’s purchase decision of Toyota Dyna and the other brands. This research is aimed to analyze is there any relation between promotion, price, and service to purchase decision of Toyota Dyna. It is continued by analysis of relationship between these three independent variables to purchase decision with business type as moderating variable. This is a quantitative research with 78 respondents as samples of Toyota Dyna users in Central Java and DIY. Questionnaires, interviews, and website are used in collecting data. Determination coefficient and Moderated Regression Analysis are used to analyze data. Result of this research is there are significant relations between promotion, price, and service to purchase decision of Toyota Dyna. Business type variable is not a moderating variable in these relationships. Advice for the company to increase sales in Toyota Dyna is develop better strategies in promotion, price, and service.